MODEL OF IMPROVING THE QUALITY OF TRAINING OF FUTURE ENGINEERING TEACHERS - Yefremova, Oksana (Professional Pedagogics, 2020)
Relevance: improvement of the system of professional training of future specialists is impossible without the introduction of information technology, new approaches to measuring the quality of the educational process, innovative diagnostic methods, as well as the use of training models as a necessary prerequisite for the competence of the graduate. Purpose: a theoretical model of improving the quality of specialists’ training, which corresponds to the author’s vision of solving this problem is developed and substantiated. Its use is shown in the educational process to improve the quality of training of future engineering teachers. Methods: theoretical; empirical (praximetric (study and analysis of work plans, training programs for future engineering teachers, tools and methods of pedagogical diagnostics, test tasks and methods of their use); the idea of ​​cybernetic method (model «black box») is used. Results: the possibilities of pedagogical diagnostics as a technology that contributes to improving the quality of training of students of engineering and pedagogical universities are clarified; the theoretical (structural) model of improving the quality of training of future engineering teachers is proposed and substantiated, the components of the model and the requirements for its development are identified and described, the system of evaluation and quality control of learning outcomes in the higher education institutions has been improved. The evaluation of the quality of professional training of future specialists has been carried out in accordance with the developed «theoretical» and «mathematical» models, without which it is impossible to solve the issue of quality management ... Conclusions: it has been theoretically proved that the proposed ’theoretical’ model of improving the quality of training is the part of the fundamental training of engineering teachers, has a practical and applied nature, and also provides a clear algorithm for effective improvement of the quality of the educational process.